From ‘‘contravention of laws’’ to ‘‘lack of rights’’: redefining the problem of informal settlements in South Africa - Huchzermeyer, Marie (Elsevier, 2004)
Informal urban land occupation in South Africa is treated in a technocratic manner, consistent with the policy of orderly urbanisation introduced in the 1980s. This approach focusses on the contravention of laws governing property and land use, and accordingly results in most cases in evictions and relocations. A new mandate of the national Department of Housing is to eradicate the phenomenon of urban informal settlements in the next 15 years. This mandate gives new justification to the deterministic approach of eviction and relocation within the government’s standardised capital subsidy programme for housing delivery. Legislation has been tightened to enable the repression of new informal land occupations. The recent housing strategy proposal for Johannesburg, which advocates a zero tolerance approach to informal land occupations, remains largely undisputed. However, the media has often sided with the urban poor in recent cases of forceful eviction. This paper argues for a new paradigm, based on the recognition of the infringement of constitutional rights that is enabled by informality. Far from seeing informal settlements as a solution to the housing problem, it draws attention to the multiple levels of exploitation that are common to residents of informal land occupations. A socially compatible approachto intervention is suggested. This starts with mechanisms to protect residents against the infringement of their constitutional rights, rather than acting on their contravention of property laws.
Keywords: Informal settlements South Africa; land occupation; orderly urbanisation; property and land use; evictions; relocations.